Aktivitas Hormon Endogen dalam Buah Anggur Muscat ofAlexandria Muda Tanpa Biji Hasill Induksi Antibiotika - Winarso Dradjad Widodo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2002)
The experiment was conducted to determine the activity of endogenous hormones in young seedless berry of Muscat of Alexandria (MOA) grapes induced by streptomycin (SM) and spectinomycin (SE). Young berries dipped in 200 ppm M or 200 ppm SE at 3 days before full-bloom and untreated berries were analyzed for the activity of . endogenous auxin, cytokinin. gibberellin and abscisic acid (ABA). The experiment was conducted at the Laboratory of ! Pomology, Faculty of Agriculture, Okayama University, Japan, from February 1999 to August 1999. Both SM and SE reatments did not affect ABA activities of young berries. Cytokinin activity were slightly decreased by SM and SE treatments at 6 days after treatment (DAT) and became more severe at J 0 and J 3 DAT The response of berry auxin activity to antibiotic treatment was similar but stronger than cytokinins. Antibiotic treatments significantly decreased the activity ofGA at 6 and 10 DAT 1 Keywords,' Antibiotics, Endogenous hormones, Spectinomycin, Streptomycin